A Pilot Study of Tailored Cognitive–Behavioral Resilience Training for Trauma Survivors With Subthreshold Distress. Issue 3 (27th April 2016) - Zalta, Alyson K.; Tirone, Vanessa; Siedjak, Jennifer; Boley, Randy A.; Vechiu, Catalina; Pollack, Mark H.; Hobfoll, Stevan E.
Abstract: This pilot study evaluated the feasibility, acceptability, and preliminary effectiveness of tailored cognitive–behavioral resilience training (TCBRT) for trauma‐exposed individuals with a variety of subsyndromal psychological symptoms. TCBRT is a brief, flexible intervention that allows individuals to select the areas they wish to target using common cognitive–behavioral change principles. There were 14 individuals (78.6% female) who were recruited from a major medical center and enrolled in the 5‐session intervention. There were 12 (85.7%) who completed all TCBRT sessions, and 2 (14.3%) who dropped out after 3 sessions. All participants reported that they received benefit from, were engaged in, and were satisfied with the intervention. Of the 12 with postintervention data, 5 of the participants demonstrated reliable increases in resilience and 6 demonstrated reliable decreases in anxiety. These improvements appeared to be maintained at 2‐month follow‐up; of the 11 participants with follow‐up data, 5 demonstrated reliable increases in resilience and 6 demonstrated reliable decreases in anxiety. Our findings suggested that TCRBT was acceptable to trauma‐exposed individuals with varying types of subthreshold distress.